Mudharabah Contract as Economic Strengthening in Indonesia (Literature Study on Islamic Financial Institutions and Community Economic Activities) - Ibrahim, Elly; Akbar, Wahyu; Mujiburohman, Mujiburohman; Rahima, Dwira (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
Mudharabah contracts are one of the most common Islamic finance partnerships. The mudharabah contract is currently widely used in Islamic financial institutions. However, in Indonesian society, especially in the context of local economic traditions and practices, it may not be as widely implemented as in formal Islamic financial institutions. This paper uses a type of normative research. However, it also applies a library research method that examines the literature, which is analyzed qualitatively using statutory, fiqh, and sociological approaches and Sharia economic contextual approaches in society. The main principle is that Islamic banking must be able to provide profit sharing to depositors of funds at least equal to or greater than the interest rates prevailing in conventional banks. Mudharaba contracts in financial institutions and society generally aim to achieve fairness, transparency, and sustainability in economic activities based on Islamic principles. The paper tries to find out how the concept of mudharbah contracts, both in financial institutions and in practice in society, is to ensure fairness regarding mudharabah contracts.